ANALISIS KESALAHAN EJAAN PADA BERITA INTERNET CNN INDONESIA EDISI JULI 2023 - ira septiani; Eli Syarifah Aeni; Yusep Ahmadi F (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to analyze and find out errors in spelling forms, word forms, punctuation marks, and capital letters in Indonesian spelling in online newspaper from internet. This study uses qualitative descriptive method that describes the result that have been found into a detailed data. The techniques used in collecting the data are reading, marking errors, identifying, analyzing, and collecting errors in misspellings. The data sources for this research are three an online newspaper from CNN Indonesia July, 2023 edition. The result of this study indicates that the most spelling error found in this newspaper are acronym. While, other errors found are errors in capital letters, commas, periods, and errors in conjunction. It can be concluded that even though news on the internet has been published, there are still many spelling errors found at that news.